On the welfare economics of climate change - Dennig, F (2014)
The three constituent chapters of this thesis tackle independent, self-contained research questions, all concerning welfare economics in general and its application to climate change policy in particular. Climate change is a policy problem for which the costs and benefits are distributed unequally across space and time, as well as one involving a high degree of uncertainty. Therefore, cost-benefit analysis of climate policy ought to be based on a welfare function that is sufficiently sophisticated to incorporate the three dimensions of aggregation: time, risk and space. Chapter 1 is an axiomatic treatment of a stylised model in which all three dimensions appear. The main result is a functional representation of the social welfare function for policy assessment in such situations. Chapter 2 is a numerical mitigation policy analysis. I modify William Nordhaus' RICE-2010 model by replacing his social welfare function with one that allows for different degrees of inequality aversion along the regional and inter-temporal dimension. I find that, holding the inter-temporal coefficient of inequality aversion fixed, performing the optimisation with a greater degree of regional inequality reduces the optimal carbon tax relative to treating the world as a single aggregate consumer. In Chapter 3 I analyse climate policy from the point of view of intergenerational transfers. I propose a system of transfers that allows future generations to compensate the current one for its mitigation effort and demonstrate the effects in an OLG model. When the marginal benefit to a - possibly distant - future generation is greater than the cost of compensating the current generation for its abatement effort, a Pareto improvement is possible by a combination of mitigation policy and transfer payments. I show that under very general assumptions the business-as-usual outcome is Pareto dominated by such policies and derive the conditions for the set of climate policies that are not dominated thus.